Serum cytokine patterns in first half of pregnancy. (July 2019) - Stokkeland, Live Marie T.; Giskeødegård, Guro F.; Stridsklev, Solhild; Ryan, Liv; Steinkjer, Bjørg; Tangerås, Line H.; Vanky, Eszter; Iversen, Ann-Charlotte
Highlights: Maternal serum cytokine levels in first half of pregnancy of 110 healthy women are presented. The included cytokines showed an overall decrease in serum concentration from first to second trimester. Chemokines are most sensitive for gestational variation. Inflammatory cytokines strongly correlate in normal pregnancy. Cytokine profiling is a sensitive measurement of gestational variation in pregnancy. Abstract: Introduction: Human pregnancy is a state of elevated maternal systemic inflammation, and pregnancy complications are often associated with a dysfunctional immune response. The network of cytokines reflects this complex immune activity, and broad serum cytokine profiling provides a new tool to understand the changes in immune status during pregnancy. Objective: This study aimed to determine how maternal serum cytokine patterns change during the first half of pregnancy. Methods: Maternal peripheral serum samples collected at a mean gestation of 10, 13, 18 and 24 weeks were included from a prospective clinical study of healthy women (n = 110) in first half of normal pregnancy. The serum samples were analysed for 27 different cytokines using multiplex magnetic bead-based immunoassays, and high sensitivity C-reactive protein (CRP) was analysed by ELISA. Serum cytokine and CRP patterns were explored with linear mixed effects models (LMM) and multilevel partial least squares discriminant analysis (PLS-DA). Results: Serum cytokine profiling provided partial overview of the maternal immune status and corresponding reference values for serum cytokine levels during the first half of pregnancy. Several cytokines decreased in concentration from first to second trimester. Cytokine pattern analysis revealed that chemokines provided the most sensitive measurement of variation with gestational age in normal pregnancies. The nine inflammatory cytokines showed the highest intra-group correlation during pregnancy, while CRP levels did not correlate with changes in the inflammatory cytokines. Conclusion: Chemokines showed the greatest gestational variation and inflammatory cytokines showed a strong intra-group correlation during the first half of pregnancy.